Antioxidant Activity of Stevia(Stevia rebaudianaL.) Leaf Powder and A Commercial Stevioside Powder - Rao, Galla Narsing (Fakultas Farmasi, Universitas Gadjah Mada, 2014)
Stevia leaf powder (SLP) and a commercial stevioside powder (CSP) were analysed for their polyphenol content, isothermal sorption behavior and their antioxidant activity was evaluated by DPPH radical scavenging activity, ferric reducing power and ABTS assay. Polyphenol contents were higher (5.6%) in SLP than in CSP (2.3%). It was observed that the SLP was non-hygroscopic and CSP was hygroscopic in nature as seen from sorption isotherms. The equilibrium relative humidity of SLP and CSP respectively was 62 and 24%. The antioxidant activity of the methanolic extracts were determined and DPPH radical scavenging activity for SLP showed 30.33% for 20 µg/ml and 52.46% inhibition at 100 µg/ml, which were slightly higher compared to CSP stevioside, which showed 29.5% and 47.64% inhibition for similar concentrations.Higher ferric reducing power was seen in CSP (0.632) than SLP (0.166) for 100 µg.The antioxidant activity measured by ABTS assay also indicated higher activity (37.5% inhibition for10 µg/ml) for SLP than CSP (39.66% for 40 µg/ml).